Green revolution in Ghana: Looking for the key under the lamp post - Nin-Pratt, Alejandro; McBride, Linden (International Food Policy Research Institute, 2013)
With renewed interest in technical change and productivity growth in the African agricultural sector, interest is growing in the lessons of Asia’s Green Revolution and in the implementation of input promotion and subsidies to promote agricultural growth. While there are several valid reasons for seeking a model for African agricultural productivity growth from the Asian Green Revolution, the abundance of natural resources in Africa compared to Asia means that the Asian lessons might have limited application across Africa.